2019
DOI: 10.1038/s41598-019-53755-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for phospholipase A2-like toxin inhibition by the synthetic compound Varespladib (LY315920)

Abstract: The World Health Organization recently listed snakebite envenoming as a Neglected Tropical Disease, proposing strategies to significantly reduce the global burden of this complex pathology by 2030. In this context, effective adjuvant treatments to complement conventional antivenom therapy based on inhibitory molecules for specific venom toxins have gained renewed interest. Varespladib (LY315920) is a synthetic molecule clinically tested to block inflammatory cascades of several diseases associated with elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 72 publications
2
55
2
Order By: Relevance
“…Following the initial description of Varespladib's capacity to inhibit PLA 2 activity of many snake venoms in vitro [7], further studies demonstrated its ability to abrogate lethality in mouse and pig models of envenoming by the venoms of the elapid snakes Oxyuranus scutellatus and Micrurus fulvius, respectively, whose neurotoxic effect is based predominantly on the action of presynaptically acting neurotoxic PLA 2 s [18,19]. Furthermore, Varespladib was effective in the inhibition of myotoxicity induced by crude venoms and isolated PLA 2 s of viperid and elapid species [20,21]. This drug was reported to inhibit the in vitro coagulotoxic effects of venoms of African spitting cobras [22].…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial description of Varespladib's capacity to inhibit PLA 2 activity of many snake venoms in vitro [7], further studies demonstrated its ability to abrogate lethality in mouse and pig models of envenoming by the venoms of the elapid snakes Oxyuranus scutellatus and Micrurus fulvius, respectively, whose neurotoxic effect is based predominantly on the action of presynaptically acting neurotoxic PLA 2 s [18,19]. Furthermore, Varespladib was effective in the inhibition of myotoxicity induced by crude venoms and isolated PLA 2 s of viperid and elapid species [20,21]. This drug was reported to inhibit the in vitro coagulotoxic effects of venoms of African spitting cobras [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Salvador et al reported the crystal structure of a complex formed by a catalytically inactive PLA 2 (MjTX-II from Bothrops moojeni) and a synthetic inhibitor called Varespladib. The complex showed the presence of the inhibitor in the hydrophobic channel of the toxin, interacting particularly with His48 and Lys49 residues [30]. We hypothesize that compounds I and II may have a similar inhibitory mechanism on the catalytically inactive PLA 2 since docking results suggest that these compounds interact with amino acids located at the hydrophobic channel of the toxin.…”
Section: Molecular Docking and Biological Testmentioning
confidence: 89%
“…Recently, Salvador et al reported the crystal structure of a complex formed by a catalytically inactive PLA2 (MjTX-II from Bothrops moojeni) and a synthetic inhibitor called Varespladib. The complex showed the presence of the inhibitor in the hydrophobic channel of the toxin, interacting particularly with His48 and Lys49 residues [30]. We hypothesize that compounds Instead, docking results suggested several favorable interactions between compounds I and II and the studied PLA 2 ; the hydrogen bond found between the donor Nδ1 of His48 and one oxygen atom of the nitro group as the acceptor is a critical interaction to explain the biological activity of both compounds, since His48 is one of the catalytic residues (Figure 4).…”
Section: Molecular Docking and Biological Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Control groups received 20 μg of Asp-49 or Lys-49 PLA 2 or 20 μg of BoaγPLI or 40 μL of 0.85% saline. Mice blood samples were collected from the tip of the tail [36] into tubes containing citrate as anticoagulant, centrifuged at 1200 g for 15 minutes and the plasma was separated. The amount of Creatine Kinase (CK) present in the samples was estimated with a commercial CK kit (Sigma), according to the manufacture's instructions.…”
Section: Myotoxicity Inhibitionmentioning
confidence: 99%